Minimum Spanning Tree Rute Shopping Mall Di Surabaya Menggunakan Algoritma Prim - Amalia, Nabila Tasya; Novianti, Fahriza; Yasmin, Yasirah Rezqita Aisyah (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
Surabaya as the second most populous city in Indonesia often carries out developments on land, one of which is the construction of a shopping center. The large number of shopping center developments has made both local and foreign residents want to visit shopping centers in Surabaya. There are 9 most popular shopping centers used in this study. The purpose of this research is to determine the shortest route between shopping centers in Surabaya by using the prim algorithm. This algorithm determines the shortest route by forming a minimum spanning tree. The results obtained in this study are the shortest travel time from 9 shopping centers is 81 minutes with a distance of 31.5 KM. Keyword: Prim Algorithm, Graph, Rute, Surabaya